2017
DOI: 10.1016/j.biopha.2017.06.067
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of tropisetron on cerulein-induced acute pancreatitis in mice

Abstract: Acute pancreatitis (AP) causes morbidity and mortality. The aim of the present study was to investigate the protective effect of tropisetron against AP induced by cerulein. Cerulein (50μg/kg, 5 doses) was used to induce AP in mice. Six hours after final cerulein injection, animals were decapitated. Hepatic/pancreatic enzymes in the serum, pancreatic content of malondialdehyde (MDA), pro-inflammatory cytokines and myeloperoxidase (MPO) activity were measured. Tropisetron significantly attenuated pancreatic inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
1
2
0
1
Order By: Relevance
“…It has been shown that pancreatic enzymes spread into the systemic circulation as a result of inflammatory changes in the pancreas and retroperitoneum. These enzymes cause damage to its own tissue and the other organs such as the liver by producing various inflammatory mediators (Gallagher et al, 2004;Rahimian et al, 2017). In this study, increases in AST and ALT levels showed that cerulein administration also caused liver damage, while thymoquinone administration to the acute pancreatitis group significantly limited the increase in hepatic enzyme levels such as AST and ALT (p<0.05, Table 2).…”
Section: Nigellasupporting
confidence: 49%
“…It has been shown that pancreatic enzymes spread into the systemic circulation as a result of inflammatory changes in the pancreas and retroperitoneum. These enzymes cause damage to its own tissue and the other organs such as the liver by producing various inflammatory mediators (Gallagher et al, 2004;Rahimian et al, 2017). In this study, increases in AST and ALT levels showed that cerulein administration also caused liver damage, while thymoquinone administration to the acute pancreatitis group significantly limited the increase in hepatic enzyme levels such as AST and ALT (p<0.05, Table 2).…”
Section: Nigellasupporting
confidence: 49%
“…observation points out the involvement of 5-HT 3 Rs in tropisetron-induced insulin secretion. In vivo, tropisetron has been shown to induce PPARg transcriptional activity and to be beneficial in cerulein-induced acute pancreatitis in mice (Rahimian et al, 2016(Rahimian et al, , 2017. These effects highlight the ability of 5-HT 3 R antagonists in regulating blood glucose levels.…”
Section: F Strokementioning
confidence: 96%
“…Tropisetron is an antagonist for 5-hydroxytryptamine (5-HT), 3 (serotonin) receptor widely used to alleviate chemotherapy associated nausea. The beneficial effects of tropisetron have been shown in multiple pathological conditions including acute pancreatitis, 1 colitis, 2 neurological diseases, [3][4][5] as well as renal, 6,7 and hepatic injuries. 8 Tropisetron also presents anti-inflammatory and antioxidative functions.…”
Section: Introductionmentioning
confidence: 99%